Like sisters on the homefront - Williams-Garcia, Rita. (New York : Lodestar Books, 1995)
Troubled fourteen-year-old Gayle is sent down South to live with her uncle and aunt, where her life begins to change as she experiences the healing power of the family.
Keywords: African Americans -- Fiction; Family life -- Fiction